Determination of Performance Accountability of Local Government Organizations in Palembang - M Thoyib; Indra Satriawan; Farida Husin; Mega Asmarani; Periansya Periansya (STKIP Singkawang, 2017)
In regional autonomy context, value for money is a bridge to deliver local government to achieve good governance. Value for money must be operated in local finance management and local budgeting. To support it, the management of public money with value for money concept, it needs regional budgeting and good local finance management. This research aims to set factors that influence performance accountability of local government organizations in Palembang. Factors that include are the influence of performance based budgeting and local financial accounting system to performance accountability as partial and simultant. This research using purposive sampling which part of nonprobability sampling of research instrument by 129 questionnaires that directly spread to 43 local government organizations in Palembang to the head of finance department revenue treasurer, and expenditure treasurer. Data of this research was analized by multiple regression using software SPSS 20.0. The result of this research show both as partial and simultant performance based budgeting and local financial accounting system have positive influence and significant to performance accountability in local government organization